Sentidos do trabalho e formas de participação : o caso da Cooperares - Cooperativa de Produtores Rurais de Agrobiodiversidade Ares do Campo, Assentamento Mário Lago, Ribeirão Preto-SP - Melo, Thainara Granero de (2015)
The problem of participation is constantly discussed in the studies about self-managed cooperatives. The participation in rural settlements was studied by different points of view, more or less optimistic, but either consensual or conclusive. In any case in the literature review we verified multiple factors that contribute for workers difficult to truly participate in this organizations, particularly because the access to credit lines and public policies to familiar agriculture are conditioned to cooperatives creation. The goal of this master’s research was think about this problem by the study of the meanings assigned by rural workers of Cooperares, a cooperative in the Mario Lago Rural Settlement, city of Ribeirão Preto, state of Sao Paulo, Brazil. In qualitative perspective, the empiric research was built by three different moments: theoretical, bibliographic and documental surveying data; cooperative meetings observation; and semistructure interviews with ten workers and two mediators, one of the Landless Workers Movement (MST) and one of the settlement’s technical assistance. The analysis was made by the triangulation of different data sources. From the relational point of view, we identified that the instrumental participation in the cooperative was produced by a pool of psychosocial forces that reinforced institutional and symbolic dependencies. Also the senses about the cooperative has not connection with the meanings of self-management work. On the other hand, the cooperative assumed recognition and belonging functions for the workers, bounded by evangelic values. This different forces revealed that the way which development rural policies in Brazil were conceived and applied reinforce an occasional cooperativism by the need to access public policies, whose participation meaning also is misused by the State to control the workers and strengthen hegemonic interests.